EFFECT OF BULB SIZE AND CHEMICAL FERTILIZATION ON GROWTH, FLOWERING AND BULBS PRODUCTION OF Iris hollandica - Alsheikly, Abd-alrahman A. (Diyala Agricultural Sciences Journal, 2013)
A study was conducted on Iris hollandiaca Var. Prof. Blaauw to investigate the effectively of 5 bulb sizes (3-4, 4-5, 5-6, 6-7, 7-8)cm and 4 levels of compound chemical fertilizer NPK (0, 50, 100, 150)ppm on the following characters: number of days to flowering , flower diameter , plant height , stem diameter , fresh weight of the flowering stem, vase life, weight of the new bulb, number of bulblets and weight of bulblets . The results showed a significant effect of bulb size on all characters studied, chemical fertilization had a significant effect on number of days to flowering, stem-diameter, fresh weight of the flowering stem and number of bulblets and its weights. There was no significant effects due to interactions between the two factors studied except the number of bulblets produced.